Effects of Edaphic (Soil) Factors on Plant Distribution in Chameli Community Forest, Bhaktapur, Nepal - Chaulagain, Sarita; Shrestha–Malla, Anjali Maiya (International Journal of Applied Sciences and Biotechnology, 2018)
Horizontal (east, centre, west) and vertical (bottom, middle and top) distribution study of plants as well as the study of edaphic factors were done in 2016 in Chameli Community Forest hill. Soil samples were taken from bottom, middle and top areas of east, centre and west reasons of the hill. During this study, Schima wallichi and Rhododendron arboreum were found dominant species and had less effect of edaphic factors. Similarly climber plants like Smilax aspara, Smilax lancaefolia, Smilax ovalifolia and Dioscorea bulbifera were absent in west area of top region which might be due to low content of moisture, pH, and phosphorous. Scutellaria repens, Sida cordifolia, Solanum nigrum, Tripterospermum volubile, Carex baccans, Heteropogan contortus etc. were absent in west areas of middle region which might be due to the effect of high % of sand, phosphorous and moisture content and has low % of silt, potassium and pH. Herbs are more dominant in bottom, trees in middle and shrubs in top region. The east area of bottom, middle and top region had more diverse vegetation. The average of organic matter percentage, nitrogen, potassium and phosphorous content was maximum in middle hill which supports the highly diversified tree species and dense forest. Phosphorous showed the most effective factor on plant distribution. Therefore, for the proper growth, functioning and abundance of plant species, edaphic factors had a significant effect and play an important role on plant distribution. Int. J. Appl. Sci. Biotechnol. Vol 6(1): 27-37